1995
DOI: 10.3354/meps120135
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of different size food particles in the natural diet of oyster larvae Crassostrea virginica

Abstract: We examined the feeding activity of planktotrophic larvae of the eastern oyster Crassostrea virginica on different size particles suspended in surface waters of 2 subestuaries of Chesapeake Bay, USA. Particle suspensions were characterized uslng particle counters and microscopic observations. At both sites, particle assemblages were dominated (in terms of particle number and volume) by particles (predominantly plankton cells) with equivalent spherical diameters <5 pm. Feeding experiments demonstrated that smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Douillet & Langdon (1993) reported that a strain of bacteria enhanced the survival and growth of Pacific oyster larvae. Picoplankton-sized particles (0.5 to 3 mm) constitute a large percentage of the food ingested by small larvae of the Eastern oyster Crassostrea virginica Gmelin (Baldwin & Newell 1995). The relative importance of the bacterial and cyanobacterial biomass in summer implies that picoplankton assemblages play important roles in the survival of planktonic oyster larvae in the study area.…”
Section: Implications Of Increased Picoplankton Abundance In Oyster-fmentioning
confidence: 99%
“…Douillet & Langdon (1993) reported that a strain of bacteria enhanced the survival and growth of Pacific oyster larvae. Picoplankton-sized particles (0.5 to 3 mm) constitute a large percentage of the food ingested by small larvae of the Eastern oyster Crassostrea virginica Gmelin (Baldwin & Newell 1995). The relative importance of the bacterial and cyanobacterial biomass in summer implies that picoplankton assemblages play important roles in the survival of planktonic oyster larvae in the study area.…”
Section: Implications Of Increased Picoplankton Abundance In Oyster-fmentioning
confidence: 99%
“…Second, Kemp et al (1990) conducted their filtration measurements during August; however, microheterotrophs may comprise a greater proportion of the particulate seston during months when primary production is minlmal . Baldwin & Newel1 (1995) recently demonstrated that veliger larvae of the eastern oyster Crassostrea virginica can ingest and digest heterotrophlc organisms. Although previous studies have shown that bacterivorous nanoflagellates can be ingested by adult suspension-feeding b~valves (for example, see Kemp et al 1990), ours is the first investigation of the ability of adult bivalve molluscs to digest and assimilate these organisms.…”
Section: Diet Culturesmentioning
confidence: 99%
“…The second is negligible grazing pressure on 2 to 20 pm phytoplankton by the larvae relative to that of other herbivores such as ciliates and crustaceans. Edible food size of the larvae overlaps that of the herbivores (Baldwin & Newell 1995), and grazing pressure on 2 to 20 pm phytoplankton by the herbivores is considerably high (Kamiyama 1994, Kuipers & Witte 1999. Bivalve larvae could grow on bacterial food (Hidu & Tubiash 1963, Douillet & Langdon 1993.…”
Section: Discussionmentioning
confidence: 99%
“…However, the former method needs skillful technique and sometimes overestimates the actual clearance rates when the estimation was based on the Daro model (Baldwin & Newel1 1991). The latter method also has limitations due to the detection limit for smaller particles using a flow cytometer (Baldwin & Newell 1995). It is difficult to detect particles with sizes < 1 pm using a low-power laser flow cytometer (Olson et al 1990, Baldwin & Newel1 1995.…”
Section: Discussionmentioning
confidence: 99%